Sustainability in Historic Urban Environments: Effect of gentrification in the process of sustainable urban revitalization - Rokhsaneh Rahbarianyazd (Alanya Hamdullah Emin Paşa Üniversitesi, 2017)
Considering the three-dimensional process of sustainability (physical- economical and social), the aim of conservation for making historic urban environment sustainable should be matched with these dimensions. Therefore, earlier conservation policies have progressed from a simple and restrictive concern with preservation to an increased concern for revitalization and enhancement. This means a physical revitalization may be short-lived and un-sustained. Within the process of revitalization, historic environments become the main locations of gentrification induced by urban revitalization which may involve social cost. Accordingly, this paper develops theoretical concepts on “sustainability in historic urban environment” with a particular emphasis on a social issue in terms of gentrification. Also with the result derived from theoretical parts concludes that social changes through gentrification contribute to sustaining the historic environments.